The Impact of Human Resource Management Practices on Project Manager Performance in Construction Projects - Choy , Bao Ying; Sarpin, Norliana; Khalid, Zailawati; Omar, Roshartini; Sallehuddin, Aina Mardia; Sabtu@Othman, Hilyati (Research in Management of Technology and Business, 2026)
Practices of Human Resource Management (HRM) are critical of the performance of employees with specific consideration on the project-based industries like construction. The role of Project Managers entails coordination of the use of resources, risk management and making sure that the project objectives are attained within the timeline, cost and quality limits. Nonetheless, poor HRM practices can influence their work and the general outcomes of the project adversely. The study focuses on exploring the application of HRM practices and how effective they are among the Project Managers in the Malaysian Building construction industry and suggest ways in which the practices can be improved. A structured questionnaire was used to conduct a quantitative research approach involving the Project Managers of G7 contractor companies at Kuala Lumpur. 125 responses (represent 27.77% response rate) were analyzed using descriptive statistics. The results show that HRM practices such as Recruitment and Selection, Training and Development, Performance Appraisal, and Compensation and Rewards are highly practiced and are rated as effective in facilitating the performance of the Project Manager. Training and development were identified to be the best practice among them. The strategies to improve the effectiveness of key HRM practices among Project Manager are transparent recruitment systems, continuous professional development, reward systems based on performance and strategic HRM integration. The research concludes that appropriate HRM practices that are well coordinated and aligned are essential in increasing performance of Project Managers and ensuring the construction project is more successful, while guiding construction organizations on how to strengthen the HR systems.